Bone cutter versus plastibell device in neonatal circumcision: A randomized trial - Ademola Olusegun Talabi; Gabriel Unimke Udie; Oludayo Adedapo Sowande; Owolabi Oni; Olusanya Adejuyigbe (EL-Med-Pub, 2020)
Background: Several techniques and devices have been described for circumcision each with its own pros and cons. The objective of this study was to compare the outcome of neonatal circumcision between bone-cutter and plastibell devices at our institution. Methods: This is a randomized trial (unregistered) conducted at the Pediatric Surgical Unit of a tertiary teaching hospital situated in a semi-urban setting, between January 2019 and December 2019. The uncircumcised neonates underwent circumcision by either bone-cutter or plastibell device. Demographic characteristics, operative time, estimated blood loss, and postoperative complications were compared. A p-value of <0.05 was considered significant. Results: The age ranged between 7 days and 30 days with a mean of 15.9±5.5 days. The mean age and weight of both groups were well matched (p >0.05). The operative time in the bone cutter technique was 4.2±0.9 minutes compared to 5.8±1.2 minutes in the plastibell device method (p <0.001). Blood loss was lesser with bone cutter (0.27 ±0.32mls versus 0.51 ±0.44mls in the plastibell device, p <0.001). The complication rates were comparable in both study groups (p =1.000). The overall complication rate was 5.8%. The penile perception score and the Hollander wound evaluation score for bone-cutter were 15.7±0.8 and 5.7±0.84 while in the plastibell device were 15.4±1.1 and 5.4±1.1, respectively (p >0.05). Conclusion: Operative time and blood loss were less with bone cutter compared to plastibell device. However, the complication rate, penile perception score, and Hollander wound evaluation scores were similar.